Impact of sustainable solid waste management on economic development – lessons from Enugu State Nigeria (2014)
Solid waste management system in Enugu State, Nigeria is inefficient and unsustainable largely due to the crude and unscientific methods employed. The current practice, process and programme of waste management in the state do not in any way conform to what is obtainable in other modern cities of the world. It is against this background that this study sought to find out the current state of solid waste management system in the state, and to identity factors that influences waste management and the type of solid waste management system that will aid economic development of the State. These objectives were addressed primarily using structured questionnaire administered to a cross section of people in three selected local government areas (Enugu East, North and South LGAs respectively). Personal interviews were also conducted to augment the questionnaire. It was observed that the solid waste management system in practice in the state is unscientific, unsustainable and at the prerogative of people in power. It was discovered that the current waste management system has no room for waste recycling, reuse and repair. There was also no provision for waste segregation and reduction at source technology. Majority of the waste is dumped at open landfill. The study also analyzed the newly proposed solid waste management system in the state and found that the proposed system will be better than the existing one if efficiently implemented. The proposed system outlined a framework of waste segregation, recycling, reuse, reduction, repair and abolition of certain polythene bags with less or no economic value. The authors recommend that a massive enlightenment campaign should be embarked upon to sensitize the people on the proposed waste management system so that they can key into it and contribute meaningful to its sustenance. There is need also to encourage the reuse of plastic bags, reduce litter, raise public awareness about environmental issues and encourage recycling as thicker bags will make recycling more economically viable the state government should also consider the option of public-private partnership which has been adopted with huge success in other climes.